The Sri Lankan Unemployment Problem Revisited - Rama, Martín, 1956- 1956- (The World Bank, 1999)
November 1999 - Unemployment in Sri Lanka is largely voluntary. The underlying problem is not a shortage of jobs but the artificial gap between good jobs and bad ones. Policy efforts should be aimed at reducing the gap between good and bad jobs by making product markets more competitive, reducing excessive job security, and reforming government policies on pay and employment. Sri Lanka's high unemployment rate has been attributed to a mismatch of skills, to queuing for public sector jobs, and to stringent job security regulations. But the empirical evidence supporting these explanations is weak. Rama takes a fresh look at the country's unemployment problem, using individual records from the 1995 Labor Force Survey and time series for wages in the economy's formal and informal sectors. He assesses, and rejects, the skills mismatch hypothesis by comparing the impact of educational attainment on the actual wages of those who have a job with the effect on the lowest acceptable wages of the unemployed. However, he finds substantial rents associated with jobs in the public sector and in private sector activities protected by high tariffs or covered by job security regulations. A time-series analysis of the impact of unemployment on wage increases across sectors supports the hypothesis that most of the unemployed are waiting for good job openings but are not interested in readily available bad jobs. In short, unemployment in Sri Lanka is largely voluntary. The problem is not a shortage of jobs but the artificial gap between good and bad jobs. Policy efforts should be aimed at reducing the gap between good and bad jobs by making product markets more competitive, by reducing excessive job security, and by reforming government policies on pay and employment.